Importance of local management for delivery of primary health care according to Alma-Ata principles - Nunes, Luceime Olivia [UNESP]; Lodeiro Castanheira, Elen Rose [UNESP]; Dias, Adriano [UNESP]; Tortorelli Zarili, Thais Fernanda [UNESP]; Sanine, Patricia Rodrigues [UNESP]; Mendonca, Carolina Siqueira [UNESP]; Casquel Monti, Jose Fernando; Lozigia Carrapato, Josiane Fernandes [UNESP]; Placideli, Nadia [UNESP]; Battistella Nemes, Maria Ines (Pan Amer Health Organization, 2018)
Objective. To describe the characteristics of the management process in primary health care units as well as the profile of managers, and to discuss the implications of these elements for the attainment of Unified Health System principles in Brazil in accordance with the propositions of the Alma-Ata Declaration. Method. This descriptive, cross-sectional study used data collected with the Primary Care Service Quality Assessment tool (QualiAB), a self-administered, web-based instrument. QualiAB was voluntarily answered by 157 unit managers from 41 municipalities in the state of Sao Paulo from October to December 2014. Results. Of 157 units, 67 (42.7%) were family health care units and 58 (36.9%) were traditional units; 95 (60.5%) were located in urban peripheries. At the time of the study, eight (5.0%) units did not have a manager and eight (5.0%) were managed by the city health secretary. Almost 80% of the managers were nurses and performed multiple tasks in addition to management. Multidisciplinary support (technical supervision as a means of continuing education) was available in 75 (47.7%) units; 60 (38.2%) units did not have any kind of multidisciplinary support. Participation in evaluative processes was mentioned in 130 (82.8%) units. The main results of evaluations were planning and reprogramming of activities with the engagement of the multiprofessional team in 40 units (25.5%) and definition of an annual activity plan in 38 (24.2%). Twenty-nine units (17.8%) did not have access to the results of evaluations. Conclusion. The study supports the importance of work process management and the need to (re)invest in training and recognition of local management as a strategy to produce primary health care that is capable of promoting health as a right and a condition of citizenship.
Keywords: Health management; health services administration; primary health care; Brazil